Hippocampal NG2+ pericytes in chronically stressed rats and depressed patients: a quantitative study. (4th May 2021) - Treccani, Giulia; Schlegelmilch, Anna-Lena; Schultz, Nina; Herzog, David P.; Bessa, Joao M.; Sotiropoulos, Ioannis; Müller, Marianne B.; Wennström, Malin
Abstract: Objective: The suggested link between major depression disorder (MDD) and blood–brain barrier (BBB) alterations supports an impact on the neurovascular unit in this disease condition. Here we investigate how pericytes, a major component in the neurovascular unit, respond to stress, stress hormones, proinflammatory cytokine and depression. Method: Hippocampal sections of chronic unpredictable stressed (CMS) rats, MDD patients and respective controls were immuno-stained against NG2, where the number of NG2+ pericytes in the molecular layer was counted. Proliferation of cultured pericytes after treatment with cortisol and IL-1β was analyzed using radioactive-labeled thymidine. Findings: The number of NG2+ pericytes was significantly higher in CMS animals than controls. Higher number of NG2+ pericytes was also detected in MDD patients, but the increase did not reach significance. IL-1β, but not cortisol, induced a significant increase in proliferation of cultured pericytes. Conclusion: Our results indicate that exposure to stressful conditions affects the hippocampal pericyte population. These findings add to our knowledge about the impact of stress on the neurovascular unit, which might be relevant for understanding the alterations in BBB found in MDD patients.